Analisis Strategi Gastrodiplomasi Korea Selatan dari Segi Peningkatan Kunjungan Wisatawan Asing di Korea Selatan (2014-2019) - Suhaida Juniarti; Alfian Hidayat; Purnami Safitri (Indonesian Journal of Global Discourse, 2021)
This study aims to determine the gastrodiplomacy strategy carried out by South Korea in supporting the country's national interests in terms of increasing foreign tourist visits to South Korea through the concept of gastrodiplomacy and soft power. This type of research is descriptive qualitative. The data used in this study are secondary data. Data collection techniques are carried out through literature study and documentation through journals, official documents obtained through official websites of organizations or official government sites, and articles from international news portals. Data analysis technique in this study uses Miles & Huberman’s three stages, namely data reduction, data presentation, and drawing conclusions. The results shows that food can be a medium of public diplomacy that can help achieve the national interests of South Korea, namely increasing foreign tourist visits to South Korea. Based on the data presented, foreign tourist visits to South Korea has increased every year. The motivation to visit Korea was 32.3 percent, far higher compared to business visit worth at 15.2 percent, learning Korean language at 9.1 percent, and visiting Korean drama locations at 5.6 percent.